2015
DOI: 10.1007/s00436-015-4638-1
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed-synthesized silver nanoparticles: an eco-friendly tool in the fight against Plasmodium falciparum and its vector Anopheles stephensi?

Abstract: Malaria, the most widespread mosquito-borne disease, affects 350-500 million people each year. Eco-friendly control tools against malaria vectors are urgently needed. This research proposed a novel method of plant-mediated synthesis of silver nanoparticles (AgNP) using a cheap seaweed extract of Ulva lactuca, acting as a reducing and capping agent. AgNP were characterized by UV-vis spectrophotometry, Fourier transform infrared (FTIR) spectroscopy, energy-dispersive X-ray spectroscopy (EDX), scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…The fluorescence counts were plotted against the drug concentration and the 50 % inhibitory concentration (IC 50 ) was determined by an analysis of dose-response curves. Results were validated microscopically by the examination of Giemsa-stained smears of extract-treated parasite cultures (Bagavan et al 2011;Murugan et al 2015h). …”
Section: Anti-plasmodial Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescence counts were plotted against the drug concentration and the 50 % inhibitory concentration (IC 50 ) was determined by an analysis of dose-response curves. Results were validated microscopically by the examination of Giemsa-stained smears of extract-treated parasite cultures (Bagavan et al 2011;Murugan et al 2015h). …”
Section: Anti-plasmodial Assaysmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, the anti-plasmodial activity of green-synthesized metal nanoparticles has been scarcely studied (Benelli 2016a, b;. For example, Murugan et al (2015h) reported that anti-plasmodial activity of seaweedsynthesized AgNP against CQ-resistant (CQ-r) and CQsensitive (CQ-s) strains of P. falciparum, IC 50 of U. lactuca extract were 57.26 μg/ml (CQ-s) and 66.36 μg/ml (CQ-r), while U. lactuca-synthesized AgNP IC 50 were 76.33 μg/ml (CQ-s) and 79.13 μg/ml (CQ-r). In addition, AgNP synthesized using Catharanthus roseus, and Couroupita guianensis are active against blood stages of P. falciparum (Ponarulselvam et al 2012(Ponarulselvam et al , 2015Subramaniam et al 2016b).…”
Section: Anti-plasmodial Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the method by Murugan et al [35], here a CQ-sensitive strain 3D7 and CQ-resistant strain INDO of P. falciparum were used in in vitro blood stage culture to test the anti-malarial efficacy of GQDs. The culture was carried out at G. Kuppusamy Naidu Memorial Hospital (Coimbatore, India).…”
Section: In Vitro Cultivation Of Plasmodium Falciparummentioning
confidence: 99%
“…Recently, a number of plant extracts and related metabolites have been exploited for efficient and rapid extracellular synthesis of mosquitocidal nanocomposites with high effectiveness, even if field conditions (e.g. [11,15,[32][33][34][35][36][37]). …”
Section: Introductionmentioning
confidence: 99%